Neonatal septic cellulitis. - Garofalo, L.; Bonifazi, E. (European Journal of Pediatric Dermatology, 2009)
Sepsis is the severest disease in a NICU. The form with early onset, which is more frequent in the full term baby (4), is more often due to Group B Streptococcus. The latter is usually present in the birth canal. This is why the guide lines for the prevention of neonatal sepsis suggest a bacteriological examination in the 35th-37th week and an intrapartum antibiotic treatment for the pregnant carriers (2). Meningitis, pneumonia, osteomyelitis, arthritis and cellulitis are the most frequent localizations after septicemia (3). In the case here reported, in absence of a positive bacteriological examination, the diagnosis of septic cellulitis was based on the positive CRP (1) and on the return to normal of CRP and skin lesion with the antibiotic treatment.